Should Institutional Conscientious Objection to Assisted Dying be Accommodated? - Kirby, Jeffrey (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
The contentious, topical debate about whether faith-based health care organizations should be granted accommodation on the basis of institutional conscientious objection to medical assistance is dying (MAiD) is addressed through a comparative analysis of arguments on both sides of the issue that references such relevant considerations as: claimed ‘moral-authority’, competing rights-based claims, obligations arising from patient welfare principles, formal justice, dissimilarity in consequences, and two illustrative arguments from analogy. The analysis leads to the conclusion that nonconditional accommodation on the basis of institutional conscientious objection to MAiD is not ethically acceptable in Canada. A compromise mechanism, consisting of a suggested set of pragmatic conditions, is proposed that could effectively balance the competing moral responsibilities that arise from this conclusion and a core assumption of the paper, i.e., that some dominant faith-based health institutions can legitimately request, and expect, that provincial/territorial governments pay them a measure of respect in their operational, health-care-delivery decision making because of these institutions’ long history of providing high quality, health care in Canada. It is further suggested that provincial/territorial governments only allow large, publicly funded, faith-based health care organizations to enact a conditional version of accommodation on the basis of institutional conscientious objection to MAiD in circumstances where the organization has entered into a formal agreement with the relevant health department to meet the proposed, compromise conditions (or a relevantly-similar set of conditions).